(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Ancient Khorezm, located in the lower reaches of the Amu Darya, developed a unique agricultural civilization shaped by its naturalgeographical conditions. This study examines Khorezm’s irrigated farming system, water management practices, and ecological harmony based on the ”Avesta”, Greco-Roman sources (Strabo, Hecataeus), and archaeol